“Eficiencia de bacillus thuringiensis en el control de spodoptera grugiperda en el cultivo de maíz (zea mays) en el Bajo Mayo” - Girano Flores, Ross Mery (2004)
The present titled investigation work "Efficiency of Bacillus thuringiensis in the Control of Spodoptera frugiperda in the Culivation of Corn (Zea corn) in the First floor May", he/she had as objectives: To determine the efficiency of Bacillus thuringiensis in the biological control in the cultivation of corn; to determine the cost of production of the different treatments and the relationship Beneficio/Costo. The experiment was developed in the fields of the Project Corn of the E.E "The Future" that is located in the Km. 14 of the highway Fernando Belaúnde Terri, District of Juan Guerra; the design of Complete Blocks was used at random, with factorial arrangement of 3 x 4 for 4 repetitions. The factors A1 = Time of application of Bacil/us thuringiensis (1; 5 and 10 days after the infestación with Spodoptera frugiperda) and A2 = Dose of Bacillus thuringiensis (0,0; 0,6; 0,8 y 1,0 Kg/Ha). The results demonstrated that to bigger dose of Bacillus thuringiensis and 72 hours after the application one has a better control of Spodoptera frugiperda in field with averages of 100; 100 and 92,04% of dead larvas for 1; 5 and 1 O days after the infestación. On the other hand with 1,0 Kg/Ha of Bacillus thuringiensis to 1 day after the infestación bigger height of plants of 197 cm. Was obtained; probably for the quick control, likewise a bigger yield of 5 548,00 Kg/Ha of corn was obtained obtaining an utility of SI. 106,27 news suns and a relationship Beneficio/Costo 1,04 overcoming statiscally to the other treatments in study.